Immediate effect of stair exercise on stiffness, tone, and pressure pain threshold of thoracolumbar fascia in individuals with lower limb amputation: A preliminary report - TATAR, YAŞAR (My University, 2022)
Background: Adaptations to the use of prosthesis in individuals with a lower limb amputation may cause changes in lumbopelvic region structures during daily life activities. Objective: To investigate the effect of stair exercise on the stiffness, tone, and pressure pain threshold (PPT) of the thoracolumbar fascia (TLF) in individuals with unilateral lower limb amputation. Design: This is a prospective preliminary study. Methods: The study was conducted in Prosthetic Orthotic Centers in Istanbul. Syrian individuals with unilateral transtibial (n 5 17) and transfemoral (n 5 15) amputation who received prosthesis and rehabilitation services at the centers between February 2020 and December 2020 were included in the study. The subjects were instructed to ascend and descend a nine-step stair one at a time at their maximum possible speed. Measurements were made before and immediately after the stair exercise. Tone and stiffness of TLF was measured using myometer. PPT was measured using algometer. Low back pain was evaluated using numerical pain rating scale. Results: In the transfemoral amputation group, PPT measurements taken immediately after stair exercise were significantly decreased in both the amputated (P 5 0.001) and intact (P 5 0.021) sides, whereas significant reduction in stiffness when compared with the prestair levels was observed only at the intact side (P 5 0.019). The change in PPT values on the amputated side was significantly higher in individuals with transfemoral amputation than those in individuals with transtibial amputation (P 5 0.011). Conclusion: The decrease in PPT values of TLF in the transfemoral amputation group was considered as a precursor sign for low back pain development. Thus, exercises and preventive rehabilitation programs targeting TLF may be needed, especially in this group.
Keywords: Sağlık Bilimleri; Sosyal ve Beşeri Bilimler; Health Sciences; Social Sciences and Humanities; Klinik Tıp (MED); Sosyal Bilimler (SOC); Clinical Medicine (MED); Social Sciences (SOC); amputation; pressure pain threshold; stiffness; thoracolumbar fascia; tone